A Comparative Study Between TPS (Think-Pair-Share) And Jigsaw Techniques to Enhance Students’ Reading Comprehension Ability - Marpaung, Glory Destiny Biantice; Pandjaitan, Nelson Balisar (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2019)
The purpose of this study is to find out the enhancement of students' reading comprehension between those who were taught using TPS (Think-Pair-Share) technique and those who are taught using the Jigsaw technique. The study discussed the recent developments in reading pedagogy. This study used a quantitative research method and comparative design by measuring the achievement of pre-test and post-test. The result of this study shows that p.value (sig) = 0.187 > Î± (0.05). Therefore, it is concluded that there is no significant difference in the student's reading comprehension ability. Even the difference is not significant, based on the mean score of the classes before and after being taught using those techniques, this study indicates that the use of Think-Pair-Share and Jigsaw can enhance students’ reading comprehension ability. The study also provides a new interpretation of existing sources on teaching method and offers new insights of teaching reading method by emphasizing collaborative learning. Keywords: TPS (Think-Pair-Share) and Jigsaw